A proteção jurídica de crianças e adolescentes no Brasil : desafios na prevenção e enfrentamento ao bullying e cyberbullying - Machado , Marieli (2025)
This dissertation analyzes the legal protection of children and adolescents in Brazil, focusing on the challenges of preventing and combating bullying and cyberbullying. The research examines the normative evolution of children's and adolescents' rights, the effectiveness of current legislation, and the difficulties in implementing public policies aimed at ensuring the full protection of this vulnerable group. The study highlights that, despite the existence of a robust normative framework, such as the Convention on the Rights of the Child, the 1988 Federal Constitution, and the Statute of the Child and Adolescent (ECA), the practical application of these standards still faces structural, institutional, and social obstacles. Among the main challenges are the weakness of oversight mechanisms, the slowness of judicial processes, insufficient public investment, and the lack of training for professionals involved in child and adolescent protection. The research shows that the criminalization of bullying and cyberbullying, through Law No. 13,185/2015 and Law No. 14,811/2024, represents progress, but it is not enough to eradicate these practices. The merely repressive approach must be complemented by educational and preventive actions, including the expansion of school awareness programs, the training of educators, and the strengthening of the psychosocial support network for victims. The dissociation between the normative recognition of the rights of children and adolescents and their implementation in practice compromises the protection of this vulnerable population. Confronting bullying and cyberbullying requires coordinated action between the State, family, and civil society, through integrated strategies that ensure not only the punishment of aggressors, but also prevention and adequate support for victims.